2019
DOI: 10.1002/adom.201801672
|View full text |Cite
|
Sign up to set email alerts
|

A New Twist for Materials Science: The Formation of Chiral Structures Using the Angular Momentum of Light

Abstract: and various applications particularly at the microscopic scale. This includes optical trapping and manipulation, [4][5][6] optical telecommunications, [7,8] quantum physics, [9] and "super-resolution" microscopy with a spatial resolution beyond the diffraction limit. [10][11][12] New applications for OAM fields have also been proposed in environmental optics and free-space telecommunication. As an example OAM states can potentially propagate though air turbulence with lower degradation than a conventional Gaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(52 citation statements)
references
References 100 publications
(137 reference statements)
1
39
0
Order By: Relevance
“…254 Moreover, among the diverse optical trapping schemes discussed in this review, in our view, several topics have great potential to find exciting future applications, such as the optical trapping of metal particles [183][184][185][186][187][188][189] and chiral particles, 52,53 vacuum levitation, structured light in waveguides, [255][256][257][258][259] optical binding and other collective motions in structured light fields, 113,185,[260][261][262] quantum optomechanics, 30 and optical trapping for multidisciplinary applications. 32 In the future, besides SLMs and DMDs, more flexible, efficient and much less expensive devices will be developed to produce structured beams, which can help build the next generation of optical trapping technology. Furthermore, acoustic trapping 30 and plasmonic trapping 252 have developed rapidly in recent years, and trapping of nanoparticles with electron beams 263,264 has emerged as well, which can find promising applications in biosciences, biosensors, and engineering as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…254 Moreover, among the diverse optical trapping schemes discussed in this review, in our view, several topics have great potential to find exciting future applications, such as the optical trapping of metal particles [183][184][185][186][187][188][189] and chiral particles, 52,53 vacuum levitation, structured light in waveguides, [255][256][257][258][259] optical binding and other collective motions in structured light fields, 113,185,[260][261][262] quantum optomechanics, 30 and optical trapping for multidisciplinary applications. 32 In the future, besides SLMs and DMDs, more flexible, efficient and much less expensive devices will be developed to produce structured beams, which can help build the next generation of optical trapping technology. Furthermore, acoustic trapping 30 and plasmonic trapping 252 have developed rapidly in recent years, and trapping of nanoparticles with electron beams 263,264 has emerged as well, which can find promising applications in biosciences, biosensors, and engineering as well.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, structured light beams with customized phase and amplitude have been successfully applied to drive the optical transport of particles in 3D trajectories by exerting optical forces arising from high intensity and phase gradients. Recently, there are several excellent review articles on this topic, [27][28][29][30][31][32][33] including optical pulling force, 28 optical transport of small particles, 29 optomechanics with levitated particles, 30 acoustic and optical trapping for biomedical research, 31 and so on. 32 More recently, advanced optical manipulation using structured light was reviewed, 33 which focused on the manipulation of transparent dielectric particles.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Optical vortices carry an annular intensity profile and orbital angular momentum (OAM), characterized by a quantum number l, which associated with its helical wavefront. [22][23][24][25][26] To date, several researchers have reported that irradiation with a continuous-wave visible optical vortex can force the helical mass transport of irradiated azo polymers to form wavefront-sensitive surface relief, i.e., chiral surface relief, facilitated by the spin angular momentum (SAM) of circularly polarized light with a helical electric field. [27][28][29][30][31] An ultrafast laser-induced two-photon-absorption (TPA) process offers the trans-cis photoisomerization of azo polymers with high spatial resolution, which could yield further advanced technologies, such as high-density rewritable data storage.…”
Section: Introductionmentioning
confidence: 99%
“…The handedness of the optical vortex is also determined by the sign of the topological charge. The optical vortex has been widely applied in a variety of fields, such as optical trapping and manipulation [6][7][8][9][10][11][12], optical metrology [13][14][15], fiber-based or free-space optical communication [16][17][18][19][20][21][22][23][24], quantum computing [25][26][27], cold atom physics [28][29][30][31][32], astrophysics [33][34][35], and material processing [36,37]. Furthermore, an optical vortex enables the twisting of a variety of materials, such as metals [38][39][40][41], semiconductors [42,43], azopolymers [44][45][46], and even liquid-resin to shape helical nano/microscale structures.…”
Section: Introductionmentioning
confidence: 99%